Preparation method of high-entropy zirconate PVD (Physical Vapor Deposition) ceramic film

High entropy zirconate PVD ceramic films were prepared by nanopowder re-granulation and cold isostatic pressing technology. Combined with physical vapor deposition technology, the problems of high-temperature stability and insufficient interface binding force of high-temperature ceramic films were solved, and high performance, high density and corrosion-resistant ceramic film preparation was achieved.

CN119638414AActive Publication Date: 2025-03-18HARBIN INST OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411992505.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In the prior art, the high-temperature ceramic films have insufficient high-temperature stability, poor interface bonding and difficult functional design, making it difficult to meet the needs of high-temperature application scenarios.

Method used

Through specific system optimization and parameter regulation, nanopowder re-granulation technology and cold isostatic pressing technology are used to prepare high entropy zirconate PVD ceramic films, combined with physical vapor deposition technology, to form ceramic films with high density, high binding force and high temperature and corrosion resistance.

Benefits of technology

It significantly improves the high temperature stability of high-entropy ceramic films, enhances interface binding force, adapts to the use requirements of multiple thermal cycles, and simplifies the target material preparation process and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638414A_ABST
    Figure CN119638414A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-entropy zirconate PVD (Physical Vapor Deposition) ceramic thin film. The preparation method comprises the following steps: carrying out spray granulation on five rare earth oxides, namely nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder, and zirconium oxide to obtain target raw material powder; screening to obtain spherical powder with different particle size ratios, manufacturing a target blank by utilizing cold isostatic pressing, and then sintering the blank target; the high-entropy zirconate EB-PVD target material is deposited on the surface of a PVD base material with the flat and smooth surface through the PVD technology, and the high-entropy zirconate PVD ceramic film is formed. The high-temperature stability of the high-entropy ceramic thin film prepared by utilizing the PVD technology is obviously improved, the high-entropy ceramic thin film can bear the environment of 1500 DEG C or above, the interface bonding force is enhanced, and the high-entropy ceramic thin film meets the use requirement of multiple thermal cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-temperature thermal protective coatings and relates to a method for preparing a high-entropy ceramic film, and specifically relates to a method for preparing a high-entropy zirconate PVD ceramic film. Background Art

[0002] High-temperature ceramic film refers to a ceramic-based film material with excellent thermal and mechanical properties in a high-temperature environment. Due to its excellent high-temperature resistance, oxidation resistance, corrosion resistance, and high hardness, high-temperature ceramic film has important application value in high-end manufacturing. For example, in the aerospace field, ceramic films are used as thermal barrier coatings for turbine blades to improve their heat resistance and oxidation resistance; in energy and industrial equipment, ceramic films can be used for key components of gas turbines and internal combustion engines to extend the service life of the equipment; in the electronics industry, ceramic films have excellent dielectric properties and thermal stability, and are suitable for high-performance electronic devices. However, traditional preparation methods (such as chemical vapor deposition, wet chemical methods, etc.) often have problems such as environmental pollution, high preparation temperature, and insufficient film uniformity, which makes it difficult to meet the needs of high-temperature ceramic films in practical applications.

[0003] Physical vapor deposition (PVD) technology is an advanced thin film preparation technology that transfers materials to the substrate surface by physical means to form a dense and uniform thin film layer. Its characteristics include low preparation temperature, strong process controllability, flexible adjustment of thin film chemical composition and low environmental pollution, which makes it occupy an important position in the preparation of high-temperature ceramic thin films. PVD includes processes such as evaporation deposition, sputtering deposition and ion plating. Ceramic films with different chemical compositions and structures can be obtained by adjusting the deposition parameters. However, in the existing technology, PVD preparation of high-temperature ceramic films still faces the following technical challenges: (1) High-temperature stability of the film: The film needs to maintain excellent mechanical properties and chemical stability in a high-temperature environment. (2) The bonding strength between the film and the substrate: During the thermal cycle process, the film is prone to peeling, and the bonding interface needs to be further optimized.

[0004] In recent years, research on the preparation of nanostructured films and multi-element ceramic films by PVD technology has made some progress. These new coatings show good application prospects in improving the high-temperature performance, thermal shock resistance and bonding strength of the films. However, for different application scenarios, the preparation technology of high-temperature ceramic films still needs to be further optimized to overcome the limitations of existing processes.

[0005] High entropy ceramic film is a new type of material developed based on the theory of high entropy alloys. Unlike traditional single or binary systems, it is composed of multiple main elements (metal or non-metal), and its complex structure is usually stabilized by entropy effect. This type of film shows significant advantages in high temperature stability, oxidation resistance, corrosion resistance and radiation resistance, and is considered to be an important solution to meet the needs of extreme working conditions. However, the complex composition and microstructure design requirements of high entropy ceramic films place extremely high demands on the preparation process.

[0006] PVD has become the preferred method for preparing high-entropy ceramic films due to its low pollution, precise control, and multiple structural design features. By controlling the deposition process parameters, PVD technology can achieve fine regulation of the film microstructure, phase composition, and chemical composition, providing an effective means for optimizing the performance of high-entropy ceramic films.

[0007] High-entropy ceramic films prepared based on PVD technology have attracted great attention in the field of materials science due to their multifunctional properties and broad application prospects. High performance of films can be achieved through reasonable material design, process optimization and structural regulation. However, in order to solve the problems of complex system design and large-scale production, it is necessary to further combine multidisciplinary technologies for collaborative innovation. In the future, with the continuous advancement of material technology and preparation technology, high-entropy ceramic films are expected to play a more important role in high-end manufacturing, energy and extreme environment applications. Summary of the invention

[0008] In order to solve the problems of insufficient high-temperature stability, poor interface bonding and difficulty in functional design of the film in the prior art, the present invention provides a method for preparing a high-entropy zirconate PVD ceramic film. The method prepares a ceramic film with high density, high bonding strength and high temperature and corrosion resistance through specific system optimization and parameter control, which is suitable for a variety of high-temperature application scenarios.

[0009] The objective of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a high entropy zirconate PVD ceramic film comprises the following steps:

[0011] Step 1: Add zirconium oxide grinding balls and appropriate amount of deionized water to the vertical ball mill, then add a certain amount of dispersant to the deionized water, and after the dispersant is completely dissolved, follow the (Sm 0.2 Eu 0.2 Tb 0.2 Dy 0.2 Lu 0.2)2Zr2O7(SETDL) shown in the ratio, add nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder, after ball milling for a period of time, add a certain amount of binder and continue ball milling for a period of time to obtain a uniform slurry, wherein:

[0012] The particle size of the nano Sm2O3 powder is 5 to 90 nm;

[0013] The particle size of the nano-Eu2O3 powder is 5 to 90 nm;

[0014] The particle size of the nano Tb2O3 powder is 5 to 90 nm;

[0015] The particle size of the nano Dy2O3 powder is 5 to 90 nm;

[0016] The particle size of the nano Lu2O3 powder is 5 to 90 nm;

[0017] The particle size of the nano ZrO2 powder is 5 to 90 nm;

[0018] The raw materials of the nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder are of 4N grade purity;

[0019] The amount of deionized water used is 0.5 to 3 times the total mass of the nanopowder;

[0020] The dispersant is sodium tripolyphosphate (Na5P3O 10 ), sodium hexametaphosphate ((NaPO3)6), sodium pyrophosphate (Na4P2O7), ammonium citrate (C6H5O7(NH4)3), sodium citrate (C6H5Na3O7), polyvinyl alcohol (PVA), polyethylene glycol (PEG), etc. One or more of the dispersant, the amount of which is 0.03-6% of the total mass of the nanopowder;

[0021] The diameter of the zirconia grinding ball is 2 to 10 mm, the amount of the zirconia grinding ball is 1 to 5 times the total mass of the nano powder, the total ball milling time is 6 to 24 hours, and the number of revolutions is 300 to 1000 revolutions per minute;

[0022] The binder is one of gum arabic (Acacia), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), tetraethyl orthosilicate (TEOS), etc., and the amount of the binder is 0.1-10% of the total mass of the nano powder;

[0023] Step 2: The slurry obtained in step 1 is subjected to spray granulation to obtain micrometer-sized nanostructured spherical rare earth oxide powder, wherein:

[0024] The parameters of the spray granulation are as follows: the air inlet temperature is set at 200-250°C, the air outlet temperature is set at 100-130°C, the peristaltic pump speed is set at 30-45r / min, and the needle passing speed is set at 10-15t / min;

[0025] Step 3: The rare earth oxide powder obtained in step 2 is screened according to the particle size, the screened spherical powders with different particle sizes are proportioned, and then pressed by cold isostatic pressing to obtain target embryos with different porosities, wherein:

[0026] The sieving specifications are 50-150 mesh, 150-300 mesh, 300-400 mesh, and the mass ratio is 2-6:1-3:1-5, and is used according to the particle size distribution of the granulated powder and its different porosity requirements;

[0027] During the pressing process, the pressure is controlled at 150-250 MPa, and the holding time is controlled at 120-300 s.

[0028] The cold isostatic pressing method can use wet bag cold isostatic pressing, dry bag cold isostatic pressing, press pre-pressing and other molding methods. Preferably, the cold isostatic pressing method is wet bag cold isostatic pressing;

[0029] Step 4: Sinter the target green body to obtain a SETDL high entropy zirconate EB-PVD target, wherein:

[0030] The sintering mechanism is as follows: first, the temperature is raised to 350°C (debinding temperature) at 1-10°C / min and kept for 300-420min, then, the temperature is raised to 1100°C at 1-10°C / min and kept for 180-250min, then, the temperature is raised to 1400°C (synthesis temperature) at 1-10°C / min and kept for 480-600min, and finally, the temperature is lowered to room temperature;

[0031] The debinding temperature is related to the types of dispersants and glue used in granulation, and the synthesis temperature is related to different high entropy systems;

[0032] Step 5: Using physical vapor deposition (PVD) technology, a high entropy zirconate EB-PVD target is deposited on a smooth and clean surface of a PVD substrate to form a SETDL high entropy zirconate PVD ceramic film, wherein:

[0033] The PVD substrate may be one of a single crystal silicon plate, a polished alloy substrate, etc.;

[0034] The parameters in the SETDL high entropy zirconate PVD ceramic film preparation process are as follows: the substrate temperature is heated from room temperature to 50-200°C, the distance between the substrate and the evaporation target (target-substrate distance) and the angle between the substrate plane normal and the deposition incident steam particles (incident angle) can be adjusted according to actual needs, the maximum target-substrate distance is 500mm, and the incident angle is set to 45°. During the coating preparation process, the electron gun high voltage is -10-4kV, and the electron gun beam current is 80-110W / cm 2 The current variation range of the scanning position (X-axis, Y-axis) is ±0.7A-±1.3A. The deposition rate is controlled by controlling the electron beam current and adjusting the size of the evaporation target material molten pool. The deposition rate can reach up to 1-5nm / min, and the deposition coating thickness is 10-500nm.

[0035] Compared with the prior art, the present invention has the following advantages:

[0036] 1. The present invention utilizes nano-powder regranulation technology and cold isostatic pressing technology to prepare SETDL high-entropy zirconate as a target material suitable for electron beam physical vapor deposition, providing a method for the implementation of this high-performance high-entropy material on thermal spray coatings.

[0037] 2. The present invention utilizes particle size classification and blending technology to press spherical powder of rare earth oxide into green embryos. In order to ensure that the overall volume shrinkage of the target material is minimized and has a certain porosity requirement, the solid phase synthesis sintering route is combined with the target material sintering route, which can strictly control the porosity and volume shrinkage, solve the problems of unstable size of the target material after sintering and poor toughness of the ceramic target material, simplify the target material preparation process, and reduce production costs.

[0038] 3. The SETDL target material prepared by the present invention has high purity, excellent mechanical properties, and a smooth coating surface structure, and can be used to replace traditional EB-PVD coating materials as high-performance thermal barrier coating materials for aircraft engines and gas turbines.

[0039] 4. The high-entropy ceramic film prepared by the PVD technology of the present invention has significantly improved high-temperature stability and can withstand environments as high as 1500°C or above. The interface bonding force is enhanced and it can adapt to the use requirements of multiple thermal cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a process flow chart for preparing high entropy zirconate PVD ceramic films;

[0041] Figure 2 This is a macroscopic structure diagram of the target material after sintering in Example 1;

[0042] Figure 3 is a cross-sectional structure diagram of the target material in Example 1;

[0043] Figure 4 It is the surface morphology and energy spectrum of the molten pool solidification after the target material evaporates in Example 1;

[0044] Figure 5 It is the surface morphology and energy spectrum of the coating in Example 2;

[0045] Figure 6 is the cross-sectional morphology and energy spectrum diagram of the coating in Example 2;

[0046] Figure 7 This is the XRD diagram of the high entropy ceramic film prepared by PVD in Example 2. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0048] Embodiment 1:

[0049] This embodiment provides a method for preparing a high-entropy zirconate PVD ceramic film, wherein five rare earth oxides, namely, nano-Sm2O3 powder, nano-Eu2O3 powder, nano-Tb2O3 powder, nano-Dy2O3 powder, nano-Lu2O3 powder and nano-ZrO2 powder, and zirconium oxide are firstly sprayed to obtain target raw material powder; spherical powders with different particle size ratios are obtained through screening, and target green embryos are made by cold isostatic pressing, and then the green embryo target material is sintered; and the high-entropy zirconate EB-PVD target material is deposited on the surface of a smooth and bright PVD substrate by physical vapor deposition (PVD) technology to form a high-entropy zirconate PVD ceramic film. Figure 1 As shown, it is specifically achieved through the following steps:

[0050] Step 1: According to (Sm 0.2 Eu 0.2 Tb 0.2 Dy 0.2 Lu 0.2 )2Zr2O7, nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder are weighed, wherein: the particle size of the nano Sm2O3 powder is 20nm; the particle size of the nano Eu2O3 powder is 20nm; the particle size of the nano Tb2O3 powder is 20nm; the particle size of the nano Dy2O3 powder is 20nm; the particle size of the nano Lu2O3 powder is 20nm; the particle size of the nano ZrO2 powder is 20nm.

[0051] Step 2: Add deionized water to a vertical ball mill, then add dispersant ammonium citrate to the deionized water, add nano-Sm2O3 powder, nano-Eu2O3 powder, nano-Tb2O3 powder, nano-Dy2O3 powder, nano-Lu2O3 powder and nano-ZrO2 powder and zirconia ball milling balls, and ball mill for 12 hours to obtain a uniform slurry, wherein: the amount of deionized water is twice the total mass of the nano-powder, the amount of ammonium citrate is 0.5% of the total mass of the nano-powder, the diameter of the zirconia grinding balls is 3 mm and 5 mm, the mass ratio is 6:4, and the mass of the zirconia grinding balls is 2.5 times the total mass of the nano-powder.

[0052] Step 3: Add gum arabic as a binder to the uniform slurry obtained in step 2 and then ball-mill for 0.5 h to obtain a uniform slurry, wherein the amount of gum arabic is 1.0% of the total mass of the nanopowder.

[0053] Step 4: Add the slurry obtained in step 3 into the agitator and obtain the agglomerate powder by spray granulation, wherein: the agitator parameter is 15 rpm, the spray granulation parameters are: the inlet air temperature is 245°C, the outlet air temperature is 120°C, the needle passing frequency is 10 times per minute, and the peristaltic pump rate is 40 rpm.

[0054] Step 5: The agglomerate powder obtained after spray granulation in step 4 is screened and screened with three specifications of 400 mesh, 200 mesh and 100 mesh. The three specifications of powder are mixed in a mass ratio of 2:2:6 and wet bag cold isostatic pressing is performed under a pressure of 200Mpa. The pressure is maintained for 120s to reduce the pre-pressing process in the early stage to obtain a target embryo with a diameter of 80mm and a height of 110mm. The particle size ratio can be appropriately changed according to different process requirements.

[0055] Step 6: Use a box-type sintering furnace to sinter the target green body, raise the temperature to 350°C (debinding temperature) at 5°C / min and keep it for 300 minutes, then raise the temperature to 1100°C at 5°C / min and keep it for 180 minutes, and finally raise the temperature to 1400°C (synthesis temperature) at 5°C / min and keep it for 480 minutes, then slowly cool it to room temperature to obtain the SETDL high entropy zirconate target.

[0056] Step 7: Select a single crystal silicon plate as the substrate, with a clean and bright surface.

[0057] Step 8: The high entropy target material sintered in step 6 is deposited on the surface of the single crystal silicon plate in step 7 by physical vapor deposition (PVD) to obtain the SETDL PVD ceramic film. The parameters in the preparation process of the SETDL high entropy zirconate ceramic film are: the substrate temperature is heated from room temperature to 120°C, the target-substrate distance is 300mm, the incident angle is set to 45°, and during the coating preparation process, the electron gun high voltage is -7.92kv, and the electron gun beam current is 102W / cm2 , the maximum current of the scanning position X-axis is -0.54A, the maximum current of the scanning position Y-axis is -0.23A, the deposition rate is 1nm / min, and the deposition coating thickness is 100nm.

[0058] In this embodiment, the macroscopic structure of the target after sintering is as follows: Figure 2 As shown by Figure 2 It can be seen that the macroscopic size meets the requirements and the surface quality is good; the cross-sectional structure diagram of the target is as follows Figure 3 As shown by Figure 3 It can be seen that the pores are evenly distributed, the pore size is evenly distributed, and there are no obvious defects inside; the surface morphology and energy spectrum of the molten pool solidified after the target material evaporates are as follows Figure 4 As shown by Figure 4 It can be seen that after electron beam melting, the molten pool has a good melting effect, the molten droplets are uniform without obvious cracks, and the elements are evenly distributed; the density and volume shrinkage of the target material are shown in Table 1.

[0059] Table 1

[0060]

[0061] Embodiment 2:

[0062] This embodiment provides a method for preparing a high-entropy zirconate PVD ceramic film, wherein five rare earth oxides, namely, nano-Sm2O3 powder, nano-Eu2O3 powder, nano-Tb2O3 powder, nano-Dy2O3 powder, nano-Lu2O3 powder and nano-ZrO2 powder, and zirconium oxide are firstly sprayed to obtain target raw material powder; spherical powders with different particle size ratios are obtained through screening, and target green embryos are made by cold isostatic pressing, and then the green embryo target material is sintered; and the high-entropy zirconate EB-PVD target material is deposited on the surface of a smooth and bright PVD substrate by physical vapor deposition (PVD) technology to form a high-entropy zirconate PVD ceramic film. Figure 1 As shown, it is specifically achieved through the following steps:

[0063] Step 1: According to (Sm 0.2 Eu 0.2 Tb 0.2 Dy 0.2 Lu 0.2)2Zr2O7, nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder are weighed, wherein: the particle size of the nano Sm2O3 powder is 20nm; the particle size of the nano Eu2O3 powder is 20nm; the particle size of the nano Tb2O3 powder is 20nm; the particle size of the nano Dy2O3 powder is 20nm; the particle size of the nano Lu2O3 powder is 20nm; the particle size of the nano ZrO2 powder is 20nm.

[0064] Step 2: Add deionized water to a vertical ball mill, then add dispersant ammonium citrate to the deionized water, add nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder and zirconia milling balls, and mill for 12 hours to obtain a uniform slurry, wherein: the amount of deionized water is twice the total mass of the nano powder, the amount of ammonium citrate is 0.5% of the total mass of the nano powder, the diameter of the zirconia milling balls is 3 mm and 5 mm, and the mass of the zirconia milling balls is 2.5 times the total mass of the nano powder.

[0065] Step 3: Add gum arabic as a binder to the uniform slurry obtained in step 2 and then ball-mill for 0.5 h to obtain a uniform slurry, wherein the amount of the binder is 1.0% of the mass of the raw material powder.

[0066] Step 4: Add the slurry obtained in step 3 into the agitator and obtain the agglomerate powder by spray granulation, wherein: the agitator parameter is 15 rpm, the spray granulation parameters are: the inlet air temperature is 245°C, the outlet air temperature is 120°C, the needle passing frequency is 10 times per minute, and the peristaltic pump rate is 45 rpm.

[0067] Step 5: The agglomerate powder obtained after spray granulation in step 4 is screened and screened with three specifications of 400 mesh, 150 mesh and 100 mesh. The three specifications of powder are mixed in a mass ratio of 5:3:2 and then wet-bag cold isostatic pressing is performed: the pressure is 200Mpa, and the pressure is maintained for 120s to obtain the target embryo. The particle size ratio can be appropriately changed according to different process requirements.

[0068] Step 6: Use a box-type sintering furnace to sinter the target green body, raise the temperature to 350°C (debinding temperature) at 5°C / min and keep it for 300 minutes, then raise the temperature to 1100°C at 5°C / min and keep it for 180 minutes, and finally raise the temperature to 1400°C (synthesis temperature) at 5°C / min and keep it for 480 minutes, then slowly cool it to room temperature to obtain the SETDL high entropy zirconate target.

[0069] Step 7: Select a single crystal silicon plate as the substrate, with a clean and bright surface.

[0070] Step 8: The high entropy target material sintered in step 6 is deposited on the surface of the single crystal silicon plate in step 7 by physical vapor deposition (PVD) to obtain the SETDL PVD ceramic film. The parameters in the preparation process of the SETDL high entropy zirconate ceramic film are: the substrate temperature is heated from room temperature to 120°C, the target-substrate distance is 300mm, the incident angle is set to 45°, and during the coating preparation process, the electron gun high voltage is -7.92kv, and the electron gun beam current is 102W / cm 2 , the maximum current of the scanning position X-axis is -0.54A, the maximum current of the scanning position Y-axis is -0.23A, the deposition rate is 1nm / min, and the deposition coating thickness is 100nm.

[0071] In this embodiment, the coating surface morphology and energy spectrum are as follows: Figure 5 As shown by Figure 5 It can be seen that the coating surface is smooth, the surface quality is good, the elements are evenly distributed, and there is no segregation diffusion; the coating cross-sectional morphology and energy spectrum are as follows Figure 6 As shown by Figure 6 It can be seen that the overall density of the coating is high, the quality is good, the elements are evenly distributed, and there is no segregation diffusion coating; the XRD pattern of the high entropy ceramic film prepared by PVD is as follows Figure 7 As shown by Figure 7 It can be seen that the phase structure is stable and there is no phase change.

Claims

1. A method for preparing a high entropy zirconate PVD ceramic film, characterized in that The method comprises the following steps: Step 1: Add zirconium oxide grinding balls and appropriate amount of deionized water to the vertical ball mill, then add dispersant to the deionized water, and after the dispersant is completely dissolved, follow the (Sm 0.2 Eu 0.2 Tb 0.2 Dy 0.2 Lu 0.2 )2Zr2O7, add nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder, and then ball mill for a period of time, add a binder and continue to ball mill for a period of time to obtain a uniform slurry, wherein: the amount of deionized water is 0.5 to 3 times the total mass of the nano powder, the amount of the dispersant is 0.03 to 6% of the total mass of the nano powder, and the amount of the binder is 0.1 to 10% of the total mass of the nano powder; Step 2: The slurry obtained in step 1 is subjected to spray granulation to obtain micrometer-sized nanostructured spherical rare earth oxide powder; Step 3, the YSZ agglomerated powder obtained in step 2 is screened according to the particle size, the spherical powders with different particle sizes after screening are proportioned, and then pressed by cold isostatic pressing method to obtain target embryos with different porosities, wherein: the screening specifications are 50-150 mesh, 150-300 mesh, 300-400 mesh, and the mass ratio is 2-6:1-3:1-5; Step 4: Sintering the target green body to obtain a high entropy zirconate EB-PVD target, wherein the sintering mechanism is: first, increasing the temperature to 350°C at 1-10°C / min and keeping it for 300-420min, then increasing the temperature to 1100°C at 1-10°C / min and keeping it for 180-250min, then increasing the temperature to 1400°C at 1-10°C / min and keeping it for 480-600min, and finally, reducing the temperature to room temperature; Step 5: Use PVD technology to deposit the high entropy zirconate EB-PVD target on the flat and smooth surface of the PVD substrate to form a SETDL high entropy zirconate PVD ceramic film.

2. The method for preparing a high entropy zirconate PVD ceramic film according to claim 1, characterized in that The particle sizes of the nano Sm2O3 powder, nano Eu2O3 powder, nano Tb2O3 powder, nano Dy2O3 powder, nano Lu2O3 powder and nano ZrO2 powder are all 5 to 90 nm.

3. The method for preparing a high entropy zirconate PVD ceramic film according to claim 1, characterized in that The dispersant is one or more of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, ammonium citrate, sodium citrate, polyvinyl alcohol, and polyethylene glycol.

4. The method for preparing a high entropy zirconate PVD ceramic film according to claim 1, characterized in that The binder is one of gum arabic, polyvinyl alcohol, carboxymethyl cellulose and ethyl silicate.

5. The method for preparing a high entropy zirconate PVD ceramic film according to claim 1, characterized in that The diameter of the zirconium oxide grinding ball is 2-10 mm, the amount of the zirconium oxide grinding ball is 1-5 times the total mass of the nano powder, the total ball milling time is 6-24 hours, and the number of revolutions is 300-1000 revolutions per minute.

6. The method for preparing a high entropy zirconate PVD ceramic film according to claim 1, characterized in that The parameters of spray granulation are as follows: the inlet air temperature is set at 200-250°C, the outlet air temperature is set at 100-130°C, the peristaltic pump speed is set at 30-45 r / min, and the needle passing speed is set at 10-15 t / min.

7. The method for preparing a high entropy zirconate PVD ceramic film according to claim 1, characterized in that During the pressing process, the pressure is controlled at 150-250 MPa, and the holding time is controlled at 120-300 s.

8. The method for preparing a high entropy zirconate PVD ceramic film according to claim 1, characterized in that The cold isostatic pressing method uses a wet bag cold isostatic pressing, a dry bag cold isostatic pressing, and a press pre-pressing molding method.

9. The method for preparing a high entropy zirconate PVD ceramic film according to claim 1, characterized in that The PVD substrate is one of a single crystal silicon plate and a polished alloy substrate.

10. The method for preparing a high entropy zirconate PVD ceramic film according to claim 1, characterized in that The parameters in the preparation process of the high entropy zirconate PVD ceramic film are: the substrate temperature is heated from room temperature to 50-200°C, the electron gun high voltage is -10--4kV, and the electron gun beam current is 80-110W / cm 2 The scanning position current variation range is ±0.7A-±1.3A, the deposition rate is 1-5nm / min, and the deposition coating thickness is 10-500nm.

Citation Information

Patent Citations

  • Piezoelectric ceramic composition

    CN101374782A

  • High-entropy oxide ultra-high-temperature thermal barrier coating prepared through EB-PVD technology and method thereof

    CN114000107A

  • Ingot for ceramic coating by physical vapor growth method and production method therefor

    JP2003342721A

  • High-entropy oxides for thermal barrier coating (TBC) top coats

    US20210347699A1

  • Medium / high-entropy ceramic material and fiber-toughened ceramic-based composite material, and preparation methods therefor and use thereof

    WO2023174160A1